2002
DOI: 10.1046/j.1467-789x.2002.00079.x
|View full text |Cite
|
Sign up to set email alerts
|

Should obese patients be counselled to follow a low‐glycaemic index diet? Yes

Abstract: A reduction in dietary fat has been widely advocated for the prevention and treatment of obesity and related complications. However, the efficacy of low-fat diets has been questioned in recent years. One potential adverse effect of reduced dietary fat is a compensatory increase in the consumption of high glycaemic index (GI) carbohydrate, principally refined starchy foods and concentrated sugar. Such foods can be rapidly digested or transformed into glucose, causing a large increase in post-prandial blood gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
91
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(95 citation statements)
references
References 100 publications
3
91
1
Order By: Relevance
“…A low-GI diet has been advocated for the treatment and prevention of overweight and obesity in the general public in the US (Ludwig, 2000;Ebbeling, 2001;Pawlak et al, 2002). While the concept of GI in body weight control is moving into the public arena, the present study has provided relevant information on the pattern of glycaemic load and the relationship between meal glycaemic load and childhood overweight in a Chinese population.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A low-GI diet has been advocated for the treatment and prevention of overweight and obesity in the general public in the US (Ludwig, 2000;Ebbeling, 2001;Pawlak et al, 2002). While the concept of GI in body weight control is moving into the public arena, the present study has provided relevant information on the pattern of glycaemic load and the relationship between meal glycaemic load and childhood overweight in a Chinese population.…”
Section: Discussionmentioning
confidence: 88%
“…While the role played by dietary GI in obesity development and treatment is still inconclusive (Pawlak et al, 2002;Raben, 2002), the evidence for GI in diabetes management seems to be substantial (Buyken et al, 2001;Gilbertson et al, 2001;Jimenez-Cruz et al, 2003). The practical utility of GI has been further suggested by the joint FAO/WHO expert consultation on carbohydrates, which had directly addressed the usage of GI in the dietary management of diabetes Adjusted for paternal obesity (BMIo25 or X25 kg/m 2 ), maternal obesity (BMIo25 or X25 kg/m 2 ), birth weight (o3.0, 3.0-3.5, X3.5 kg), sleeping (9, 9-11 or X11 h/day), mean energy intake (o1600 or X1600 kcal/day) and father as a current smoker (yes or no).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to obesity that has reached to epidemic proportions, the efficacy of low-fat diets has been questioned in recent years and instead the hypothesis has been focused on the intake of high-GI foods (Ludwig, 2000;Brand-Miller et al, 2002;Pawlak et al, 2002). Various studies have demonstrated positive acute effect of low-GI food, for example, increased satiety in healthy subjects (Granfeldt et al, 1994;Liljeberg and Björck, 1998;Ö stman et al, 2005) and decreased voluntary food intake in obese subjects (Ludwig, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The role of glycaemic index (GI) on satiety sensation and weight maintenance has been the subject of a number of studies as reviewed by for example, Ludwig (2000), Pawlak et al (2002) and Raben (2002). However, the conclusions regarding a potential relationship differ.…”
Section: Introductionmentioning
confidence: 99%